Análise do controle da lei de drogas sobre práticas jurídicas em processos judiciais - Cortes, Bruno Vieira de Macedo (2020)
The objective of this work is to evaluate the law and legal practices for the control of drug use and trafficking. Two studies were carried out: the first one aimed to analyze the meta-contingencies described in Law 11343/2006, which refers to the prevention of use, health care and social reintegration of drug addicts and the repression of trafficking of drugs. The analyzed law articles were organized into three-term contingencies, which were classified as complete or incomplete. A majority of complete contingencies have been identified. Problems were also identified in the description of criteria to distinguish traffickers and users, which can lead to problems of judgments and penalties. Given this result, there is a need to better analyze the stimuli that control judicial decisions related to drug use and dealing. The second study aimed to identify variables that control the imposition of the penalty provided for in the legislation for trafficking or possession for drug use, through the analysis of legal processes in the state of São Paulo. Relevant variables were identified as criteria related to the circumstance of the occurrence (seizure of goods, vehicles or items that can serve to measure and package drugs or flagrant of drug supply) and the defendant's past (criminal record, complaints or lawsuits). It was also observed that half of the defendants considered users were arrested until the trial analyzed. A predominance of aversive consequences was also identified in relation to referrals to educational programs for users. The importance of observing what is done to change the environment that led the person to use drugs and to start dealing drugs was discussed, since aversive control alone can have hygienist functions, in addition to producing unwanted by-products